2x+6=21-3

Simple and best practice solution for 2x+6=21-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=21-3 equation:


Simplifying
2x + 6 = 21 + -3

Reorder the terms:
6 + 2x = 21 + -3

Combine like terms: 21 + -3 = 18
6 + 2x = 18

Solving
6 + 2x = 18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2x = 18 + -6

Combine like terms: 6 + -6 = 0
0 + 2x = 18 + -6
2x = 18 + -6

Combine like terms: 18 + -6 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| 2x-x+5x-9= | | 0.6a+5-0.3a-7= | | 2y-3.5=6.5 | | 5z=2.9+3.6 | | m^2+3m-3=0 | | 0=y^2+2y-96 | | 5=5-5t | | 3x-21=5x-5 | | -4x+-4-9=-12x+11 | | 35=8-9y | | -p^2-2p=0 | | 2(j-7)=64 | | 3y-8=9 | | 2x+4(x+3)=36 | | 4e^3x+6=30 | | -3x-3x=26-2 | | 8c-13=3c+36 | | 2u^2-3u=0 | | -9=k-5k+7 | | 4x^2-15=25 | | 6t+17-3t=38 | | -6w+14=-76 | | 11x+22x-2y+54y= | | 0.5a-5-0.5a= | | -f^2+5f=0 | | 3-8p=29 | | 6(x+3)-9(x-1)=5-(X+3) | | 6t+17-3r=38 | | n-2n=n-4 | | 7r^2-5=0 | | G+14.8=45 | | 4x-2y=1forsubjecty |

Equations solver categories